ROSE GERANIUM ESSENTIAL OIL RESTORATIVE POTENTIAL ON LEAD ACETATE INDUCED OVARY TOXICITY USING A MOUSE MODEL - Madouche, Massinissa; Boulila, Nacera; Lakabi, Lynda; Akdader, Samira; Medjdoub-Bensaad, Ferroudja (Polish Journal of Natural Sciences, 2024)
It is well known that lead cause tissue damage, dysfunction of folliculogenesis and elevated follicular. Rose geranium essential oil has anti-inflammatory and antioxidant properties and could have therapeutic potential. 18 adult BALB/c mice were used in this study and divided into 3 groups. Group I received physiological water, groups II and III received a single low dose of lead acetate and after 7 days, group III received daily dose of 300µl/Kg of essential oil. Histological samples from group (II) treated with 8mg/Kg of lead acetate reveals altered ovarian structure and those of group (III) treated with 300µl/Kg of geranium essential oil showed an improved ovarian structure. Antral follicles atresia is higher in group (II) than in the other two groups. Our results indicate that a treatment with daily doses of rose geranium essential oil improved the lead-altered ovarian structure and reduced the degeneration of antral follicles.